Peace within yourself : the meaning of the book of John - Murphy, Joseph, 1898-1981 (G & D Media, 2019)
Based on the book of John, Dr. Murphy explains how you can use the most powerful, spiritual medicine in the world to bring peace, health, harmony, and abundance into your life.